2015
DOI: 10.1099/mic.0.000047
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic nitrification and aerobic denitrification at low nutrient conditions by a newly isolated bacterium, Acinetobacter sp. SYF26

Abstract: A new strain, named SYF26, was isolated from the Hei He oligotrophic drinking-water reservoir in China. Based on its phenotypic and phylogenetic characteristics, the isolate was identified as a species of genus Acinetobacter. Strain SYF26 was able to grow at low NH 4 + -N concentrations (5.46 mg l "1 ), and the nitrification rate was 0.064 mg NH 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(19 citation statements)
references
References 29 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…This result was consistence with the strain of Acinetobacter sp. CN86, in which the nitrate removal rate was lower slightly when the pH increased from 7.0 to 9.0 [ 43 ], but conflicted with another papers which reported that the nitrate reduction occurred under circumneutral pH or weak acidic conditions [ 44 , 45 ]. Compared with the degradation of nitrate, the value of pH arranging from 7.0 to 10.0 had no distinctively effect on total nitrogen removal ability of strain J with the removal percentage about 84.0%.…”
Section: Resultsmentioning
confidence: 99%
“…This result was consistence with the strain of Acinetobacter sp. CN86, in which the nitrate removal rate was lower slightly when the pH increased from 7.0 to 9.0 [ 43 ], but conflicted with another papers which reported that the nitrate reduction occurred under circumneutral pH or weak acidic conditions [ 44 , 45 ]. Compared with the degradation of nitrate, the value of pH arranging from 7.0 to 10.0 had no distinctively effect on total nitrogen removal ability of strain J with the removal percentage about 84.0%.…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of heterotrophic nitrification are that nitrification and denitrification take place simultaneously at high organic loadings, and this simultaneous nitrification/denitrification helps to avoid acidification of the reactor (Chen and Ni 2011 ; Su et al 2015 ). Many microorganisms isolated from wastewater treatment systems, including Paracoccus denitrificans , Alcaligenes faecalis , Pseudomonas sp., Thauera sp., Rhodoferax ferrireducens , Rhodococcus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, many studies do not report the degree of aggregation of cells, for example while reporting so-called “aerobic denitrification” (Takaya et al, 2003, Robertson et al, 1989, Chen et al, 2003; Khardenavis et al, 2007; Su et al, 2015). Diffusion of oxygen towards single bacterial cells is so effective that with the reported cellular respiration rates, a single aerobic cell can never deplete all the oxygen in its immediate surroundings, unless the bulk oxygen concentration is in the low nanomolar range (Schulz & Jørgensen 2001; Stolper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%